Pakai Lavli - Hakimi, Halim (Universiti Putra Malaysia Press, 2022)
The COVID-19 pandemic has caused many people to live in an ambiguous norm situation. People today are either searching to recover or are found to be recorded with uncertainty while fitting the new norm of living amidst the pandemic into their daily schedule. People are hoping to survive and feel secure within their own space. Additionally, many people are also hoping to search for a new form of energy to build the "self' in situations of coping with uncertain information reflected from the digital media environment, along with a manner that is provocative, slandering and, full of comical parody. Yet the information is slowly shifting into a language of order and disorder, between the believed and disbelieved, discomfort and fear moving towards situations that have affected the normal behaviour. The exhibition 'Breathing the Waves focuses on the idea of distance. It tries to cross a new cultural border about imagination and spatial representation between two places in re-locating the visual image to a different setting. The exhibition is a suggestion on how breathing the waves will be presented and speculates a new distance within artistic creation, which might construct interrelation,communication, and the discovery of various deliberate meanings. The artists are portraying the passion of the imaginary and how to put in place a new fiction of thought. The Academy of Fine Arts in Gdansk provides a destination in relating the imagination of place as a reality and is brought together to relocate the artwork to different readers.